A Novel Fast CU Encoding Scheme Based on Spatiotemporal Encoding Parameters for HEVC Inter Coding - Ahn, Sangsoo; Lee, Bumshik; Kim, Munchurl (IEEE transactions on circuits and systems for video technology, 2015)
Recently, a new video coding standard, High Efficiency Video Coding (HEVC), has shown greatly improved coding efficiency by adopting hierarchical structures of coding unit (CU), prediction unit (PU), and transform unit (TU). To best achieve the coding efficiency, the best combinations of CU, PU, and TU must be found in the sense of the minimum rate-distortion (R-D) costs. Owing to this, a large computational complexity occurs. Among these CU, PU, and TU, the determination of CU sizes most significantly affects the R-D performance of HEVC encoders, which causes large computational costs in operation with PU and TU size determinations. In spite of recent works in the complexity reduction of HEVC encoders, most of the research has focused on the complexity reduction with fast CU split in intra slice coding and with early TU split in both intra and inter slice. In this paper, we propose a fast and an efficient CU encoding scheme based on the spatiotemporal encoding parameters of HEVC encoders, which consists of an improved early CU SKIP detection method and a fast CU split decision method. For the current CU block under encoding, the proposed scheme utilizes sample-adaptive-offset parameters as the spatial encoding parameter to estimate the texture complexity that affects the CU partition. In addition, the motion vectors, TU size, and coded block flag information are used as the temporal encoding parameters to estimate the temporal complexity that also affects the CU partition. The proposed scheme effectively utilizes the spatiotemporal encoding parameters that are the byproducts during the encoding process of HEVC without additionally required computation. The proposed novel fast CU encoding scheme significantly reduces the total encoding time with negligible RD-performance loss. The experimental results show that the proposed scheme achieves the total encoding time savings of average 49.6% and 42.7% only with average 1.4% and 1.0% bit-rate losses for various test sequences under random access and low delay B conditions, respectively. The proposed scheme has an advantage on the implementation for parallel processing in pipeline structures of HEVC encoders due to its independency with neighboring CU blocks.